'Clickable lectins': bioorthogonal reactive handles facilitate the directed conjugation of lectins in a modular fashion. Issue 2 (15th February 2019) - Tobola, Felix; Sylvander, Elise; Gafko, Claudia; Wiltschi, Birgit
Abstract : Lectins are carbohydrate-binding proteins with specificity for their target ligands. They play diverse roles in cellular recognition and signalling processes, as well as in infections and cancer metastasis. Owing to their specificity, lectins find application in biotechnology and medicine, e.g. for blood group typing, purification of glycoproteins or lipids and as markers that target cancer cells. For some applications, lectins are immobilized on a solid support, or they are conjugated with other molecules. Classical protein conjugation reactions at nucleophilic amino acids such as cysteine or lysine are often non-selective, and the site of conjugation is difficult to pre-define. Random conjugation, however, can interfere with protein function. Therefore, we sought to equip lectins with a unique reactive handle, which can be conjugated with other molecules in a pre-defined manner. We site-specifically introduced non-canonical amino acids carrying bioorthogonal reactive groups into several lectins. As a proof of principle, we conjugated these 'clickable lectins' with small molecules. Furthermore, we conjugated lectins with different ligand specificities with one another to produce superlectins. The 'clickable lectins' might be useful for any process where lectins shall be conjugated with another module in a selective, pre-defined and site-specific manner.